2016
DOI: 10.1186/s12906-016-1200-3
|View full text |Cite
|
Sign up to set email alerts
|

Red pitaya juice supplementation ameliorates energy balance homeostasis by modulating obesity-related genes in high-carbohydrate, high-fat diet-induced metabolic syndrome rats

Abstract: BackgroundRed pitaya (Hylocereus polyrhizus) or known as buah naga merah in Malay belongs to the cactus family, Cactaceae. Red pitaya has been shown to give protection against liver damage and may reduce the stiffness of the heart. Besides, the beneficial effects of red pitaya against obesity have been reported; however, the mechanism of this protection is not clear. Therefore, in the present study, we have investigated the red pitaya-targeted genes in obesity using high-carbohydrate, high-fat diet-induced met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…In fact, previous research showed the potential role of whole fruit in reducing obesity symptoms from its relatively low level of energy density and high content of dietary fiber [49]. It can thus be suggested that the mechanism of body weight reduction is due to the metabolic effects of fiber which increase the nutrient breakdown and release from the foods and contribute to satiating effect [50] as shown in our previous study [51].…”
Section: Discussionmentioning
confidence: 61%
“…In fact, previous research showed the potential role of whole fruit in reducing obesity symptoms from its relatively low level of energy density and high content of dietary fiber [49]. It can thus be suggested that the mechanism of body weight reduction is due to the metabolic effects of fiber which increase the nutrient breakdown and release from the foods and contribute to satiating effect [50] as shown in our previous study [51].…”
Section: Discussionmentioning
confidence: 61%
“…In mice with diet-induced obesity, red pitaya-derived betacyanin treatment modulates the gut microbiota, including reducing the ratio of Firmicutes to Bacteroidetes and increasing the relative abundance of Akkermansia [ 27 ]. Dietary red pitaya juice also exhibits anti-inflammatory activities in mice with metabolic syndrome [ 43 ]. Therefore, PPE supplementation may also protect against ethanol-induced hepatic inflammation through the gut–liver axis.…”
Section: Discussionmentioning
confidence: 99%
“…Total body fat was measured as the sum of the following individual fat pad weights: epigonadal fat + retroperitoneal fat + visceral fat. Adiposity index (%) was calculated as follows: ([retroperitoneal fat (g) + visceral fat (g) + epigonadal fat (g)] / [body weight (g)]) × 100 and expressed as adiposity percentage [28]. The adiposity index was used as a measure of adiposity, because the fat degree tends to increase gradually with obesity.…”
Section: Adiposity Indexmentioning
confidence: 99%